Pengaruh Kualitas Informasi Terhadap Minat Beli Ulang Pada Aplikasi Tiktok Shop Pada Mahasiswa Fakultas Ekonomi Universitas Sumatera Barat - Dedi Mardianto (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research is entitled the effect of information quality on repurchasing interest in the tiktok shop application. This research is motivated by the rise of technological developments that cause changes in human life patterns including changes in behavior and information obtained by the community. The Tiktok application has recently been very popularly used by the community, including when meeting the needs of human life. However, it is still not in accordance with human desires because there are still many quality deficiencies, both information quality and product quality offered. The population in this study were all students who used an unknown number of tiktok applications. According to Rosco, the right sample size is more than 30 people. So the researchers took a sample of 35 people with the accidental sampling technique. The method used is Simple Linear Regression. The result of the equation is Y ̂=83.6+0.74X . The degree of relationship or Pearson correlation between variables X and Y is 69.2% which is categorized as having a fairly high relationship. While the results of the F test obtained a calculated F of -12.3 and an F table of 3.98, because the calculated F results were smaller than the F table, which means that the information quality variable had no effect on the variable of repurchase intention.